Can we use surface uplift data for reservoir performance monitoring? A case study from In Salah, Algeria. (September 2018) - Bohloli, Bahman; Bjørnarå, Tore Ingvald; Park, Joonsang; Rucci, Alessio
Highlights: Surface uplift data around In Salah CO2 injection wells are presented. Surface uplift occurs above all three wells in response to the pressure build-up. The rate of surface movement is higher in the beginning of the injection period. Analysis of surface uplift suggests satellite data may be used to monitor reservoir performance. Abstract: This paper presents surface movement (uplift and subsidence) analysis around three CO2 injection wells at In Salah, Algeria. Analysis of surface movement is based on the InSAR data acquired throughout the injection period from 2004 to 2011. This paper focuses on the detail surface deformation patterns for all three injectors throughout the injection period, and eventually correlates such patterns to the CO2 injection history. Surface uplift has a higher rate in the beginning of the injection period but levels off later on and reaches a final uplift of about 15–22 mm above different wells. We will explore whether surface movement data can reveal signatures of injection regime (i.e. matrix and fracture injections) in the reservoir. Surface movement, for a few selected points at different distances from the wellhead, and the injection pressure are plotted versus time to explore their relationship. Analysis of the plots show that surface subsidence coincide with fracture injection for some points and at certain times whereas it coincides with matrix injection for others. We also tried to map out possible time delay between injection shut-in and surface subsidence. It is learned that quantification of such a delay as well as monitoring the response of surface to fracturing in the reservoir requires high resolution surface movement data. This study shows the potential of satellite survey for monitoring the injection regime and behavior of reservoir and overburden.